Conflict Resolution of Community Land Use in PT. Musi Hutan Persada (MHP) Industrial Plantation Forest - Ruri Tria Putri; Lulu Yuningsih; Heripan; Jun Harbi (Universitas Muhammadiyah Palembang, 2024)
Uncertainty over forest area is one of the obstacles to effective forest governance in Indonesia. Of the total forest area of 130 million hectares, only about 12 percent (14.2 million hectares) has been demarcated. This uncertainty triggers tenurial conflicts with various parties with an interest in the forest area. The low income of the community triggers forest encroachment activities. Forest encroachment is a very effective alternative job according to the community to get a high income in a short time. As a result of the crisis, there was a conflict between the community around the concession area and PT Musi Hutan Persada (MHP). This research was conducted to find out and describe the pattern of land tenure by the community in the PT MHP permit area, analyze the form of partnership collaboration between communities, and find out the impacts and benefits of the collaboration scheme used. This research method is descriptive qualitative with data collection techniques of observation, interviews, documentation and literature. The triangulation technique was carried out by conducting in-depth interviews directly with selected informants. The results of this study show that based on the steatment area, the land controlled by the community can be divided into 2 land tenure patterns, namely land tenure patterns that have a steatment area of more than 50 ha with a total area of 47,568.64 ha and land tenure patterns that have a steatment area of less than 50 ha with a total area of 382.7 ha. Conflict resolution carried out by PT MHP on land that has a steatment area of more than 50 ha is managing forests with the community while land that has a steatment area of less than 50 ha is managing community forests. The impacts and benefits of the collaboration scheme carried out by PT MHP are the benefits for the company of establishing good relations between the company and the community, reducing fire levels, returning land that was once controlled by the community and not creating new conflicts.